Cold stress adaptation in Trifolium ambiguum: physiological and transcriptomic insights - Cao, Kefan; Zhang, Huimin; Ma, Yiming; Huang, Fan (Frontiers in Plant Science, 2025)
IntroductionCold stress significantly affects the growth and distribution of leguminous forage crops. Trifolium ambiguum, a cold-tolerant perennial clover, exhibits distinct physiological and molecular responses to cold stress. Understanding its cold adaptation mechanisms is crucial for improving the resilience of forage crops.MethodsIn this study, we analyzed the physiological and transcriptomic responses of T. ambiguum seedlings exposed to 0°C for 0, 2, 6, and 12 hours. Various physiological parameters, including antioxidant enzyme activities (SOD, POD, and CAT), proline, and soluble sugar levels, were measured. Transcriptomic analysis was performed to identify the gene expression changes associated with cold stress.ResultsThe results indicated that antioxidant enzyme activities (SOD, POD, and CAT) significantly increased early in response to cold stress, while proline and soluble sugar levels gradually accumulated, suggesting oxidative defense and osmotic adjustment. Transcriptomic analysis revealed that, during the early stage of cold stress, genes involved in antioxidant metabolism and photosynthesis were upregulated. As the stress persisted, metabolic processes were suppressed, followed by the activation of genes related to flavonoid biosynthesis in the later stages, which helped enhance stress tolerance.DiscussionThese findings provide insights into the cold adaptation mechanisms of T. ambiguum. The early upregulation of antioxidant and photosynthesis-related genes, along with the activation of flavonoid biosynthesis pathways later on, suggests a complex and staged response to cold stress. These insights could inform the breeding of cold-resistant forage crops, contributing to more resilient leguminous species in colder climates.